Synthesis and Biological Activities of Some New Derivatives Based on 2-amino-5-mercapto-1, 3, 4-Thiadiazole Containing Imide, β-Lactam Rings - Iftikhar Ahmed Hussein (Journal of Global Pharma Technology, 2016)
New series of 2-amino-5-mercapto-1,3,4-thiadiazole derivatives compounds are synthesized [S1-S4], then converted to Schiff′s base [S5-S10] which is reacted with chloro acetyl chloride due to the existence of ????-Lactam compound[S11-S16]. The prepared derivatives are identified by infrared spectra studies, 1HNMR, and physical properties. The antibacterial strains have been investigated: an activity has been shown against Gram (+ve) bacterial (stapylococus and Gram (- ve) bacteria (Esherichiacoli).Key words: 1, 3, 4-Thiadiazole, Schiff bases, Heterocyclic rings, Biological activity.